2014
DOI: 10.1179/1743294414y.0000000285
|View full text |Cite
|
Sign up to set email alerts
|

Influence of unmelted nanoparticles on properties of YSZ nano-coatings

Abstract: In this work, yttria stabilised zirconia (YSZ) based thermal barrier coatings (TBCs) were deposited by a supersonic atmospheric plasma spray (SAPS). The influence of the unmelted nanoparticles on the thermomechanical properties of the nanostructured YSZ coatings was studied by heat insulation and thermal shock tests. The results indicated that nanostructured SAPS-coatings consisted of nano/micro-grains (60-150 nm) and unmelted nanoparticles (20-50 nm) and exhibited a bimodal microstructure. When the unmelted n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A single ceramic material can be challenging to fulfil all of the coated ceramic materials' conditions, using a mixture of two or more ceramic materials to overcome these situations. In addition to yttria-stabilized zirconia in the range of 6-8 wt.%, this gives the topcoat powder grains better performance because of its comparatively lower density, lower thermal conductivity and higher concentration for point defects [15]. Many researchers want to develop the YSZ coating structure's excellent quality, which improves the components' durability and reliability at a higher working temperature [16].…”
Section: Topcoatmentioning
confidence: 99%
“…A single ceramic material can be challenging to fulfil all of the coated ceramic materials' conditions, using a mixture of two or more ceramic materials to overcome these situations. In addition to yttria-stabilized zirconia in the range of 6-8 wt.%, this gives the topcoat powder grains better performance because of its comparatively lower density, lower thermal conductivity and higher concentration for point defects [15]. Many researchers want to develop the YSZ coating structure's excellent quality, which improves the components' durability and reliability at a higher working temperature [16].…”
Section: Topcoatmentioning
confidence: 99%
“…Both micro-and nano-level technologies were present in the YSZ employed in the thermal spray method [2][3][4]. Initially, physical vapour deposition (PVD), chemical vapour deposition (CVD), and electron beamassisted PVD (EB-PVD) sputtering techniques were used to deposit thermal barrier coatings [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…YSZ thermal barrier coatings (TBCs) deposited using atmospheric plasma spraying on nicked-based superalloy DZ125 substrate were examined by Wang et al and found that the type of bonding, metallurgical structure, and YSZ coatings' porosity had improved [1]. e source of YSZ for the thermal spray process is in the form of micro-level and nano-level technology [2][3][4]. Initially, thermal barrier coatings are deposited using sputtering methods like physical vapour deposition (PVD), chemical vapour deposition (CVD), and electron beam assisted PVD process (EB-PVD) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%